Comparative Transcriptomic Analysis Reveals Novel Insights into the Adaptive Response of Skeletonema costatum to Changing Ambient Phosphorus - Zhang, Shu-Feng; Yuan, Chun-Juan; Chen, Ying; Chen, Xiao-Huang; Li, Dong-Xu; Liu, Jiu-Ling; Lin, Lin; Wang, Da-Zhi (Frontiers in Microbiology, 2016)
Phosphorus (P) is a limiting macronutrient for diatom growth and productivity in the ocean. Much effort has been devoted to the physiological response of marine diatoms to ambient P change, however, the whole-genome molecular mechanisms are poorly understood. Here, we utilized RNA-Seq to compare the global gene expression patterns of a marine diatom Skeletonema costatum grown in inorganic P-replete, P-deficient, and inorganic- and organic-P resupplied conditions. In total 34,942 unique genes were assembled and 20.8% of them altered significantly in abundance under different P conditions. Genes encoding key enzymes/proteins involved in P utilization, nucleotide metabolism, photosynthesis, glycolysis and cell cycle regulation were significantly up-regulated in P-deficient cells. Genes participating in circadian rhythm regulation, such as circadian clock associated 1, were also up-regulated in P-deficient cells. The response of S. costatum to ambient P deficiency shows several similarities to the well-described responses of other marine diatom species, but also has its unique features. S. costatum has evolved the ability to re-program its circadian clock and intracellular biological processes in response to ambient P deficiency. This study provides new insights into the adaptive mechanisms to ambient P deficiency in marine diatoms.